To tell or not to tell: exploring Malaysian teachers' perceptions towards storytelling in English classrooms - Yahya, Husna; Mohamed Razali, Abu Bakar; Baki, Roselan (Human Resource Management Academic Research Society, 2018)
This qualitative study explores the in-service teachers’ perceptions towards storytelling as a pedagogical strategy and also examines how and to what extent storytelling is being used as a teaching tool in Malaysian English classrooms. This study is guided by three research questions: 1) How are storytelling strategies perceived and used among the teachers to teach English in the classrooms?; 2) How often do teachers use the storytelling strategies in their lessons and for what purpose; and 3) What challenges do teachers experience while working with the storytelling strategies in their lessons, and how do they deal with these challenges? Three primary school teachers from Melaka Tengah District, Melaka were chosen via purposive sampling and from the semi-structured interview conducted, the researchers found that the teachers have a very positive outlook on using storytelling as one of the teaching strategies. However, challenges like insufficient training, time constraint, students’ low proficiency, and exam-oriented and rigid education system hinder them from fully utilising this strategy in their teaching practice. This paper discusses several implications and provide several suggestions to alleviate these concerns and to promote the use of storytelling in the teaching of English.